Buku Panduan Guru Keterampilan Pembuatan Boneka Hortikultura (Horta) bagi Siswa Tunarungu - Fauzi, Muhammad Rizqianto; Wijiastuti, Asri; Andajani, Sri Joeda (Jurnal Pembelajaran dan Riset Pendidikan, 2023)
The aim of this study; (1) produce a teacher's manual on horticultural doll-making skills for deaf students that are suitable for use; (2) to describe the feasibility of the teacher's manual for the skills of horticultural doll making for deaf students. This research is a development research, according to the steps taken by the development of Thiagarajan, Semmeln and Semmel with the 4-D model, however the researcher modifies it to 3-D, collecting data using a media validation questionnaire, validating material and validating PLB experts. The results showed that the product developed in terms of material aspects, general instructions for books, lesson plans, and learning assessment tools. The results obtained from the material expert validators were 97.8%, the results obtained from the media expert validators were 96.8% and the results obtained from the PLB expert validators were 95.7%. Based on the results of the material validator, media and PLB experts, the guidebook for making horticultural dolls is said to be valid and can be used in the skills learning process for deaf students.